A Relationship of Bleeding Manifestation with Platelet Counts in Dengue Patients in a Tertiary Care Hospital - Jamil, Muhammad; Iqbal, Javeria; Iqrash Qureshi, Hafiz Ahmad; Waheed, Ayesha; Rashid, Mariyam; Ahmed, Adeel; Jamil, Muhammad Irfan (Indus Journal of Bioscience Research, 2025)
Background and Objective: Dengue fever is a prevalent cause of febrile illness, often associated with thrombocytopenia and bleeding manifestations. The study aims to investigate the relationship between platelet counts and bleeding manifestations among dengue patients admitted to a tertiary care hospital. Material & Methods: A Cross-sectional study was conducted at the Department of Medicine, Nishtar Hospital, Multan, involving 140 confirmed dengue cases with platelet counts below 150,000/µL. This study was conducted over a period of 15 months from July 2023 to September 2024. Patients were categorized by platelet levels and bleeding manifestations and data were analyzed using SPSS version 26. Results: A total of 140 patients with a mean age of 44.23 ± 11.95 years were included in the study. Bleeding manifestations were observed in 57.1% of patients, categorized as single-site bleeding in 36.4% and multiple-site bleeding in 20.7%. Petechiae were the most common manifestation (52.1%), followed by purpura (39.3%) and gum bleeding (37.1%). Severe thrombocytopenia was significantly associated with petechiae (65.6%, p=0.042) and purpura (75.0%, p=0.000), while melena was more frequent in mild thrombocytopenia (35.6%, p=0.000). Hematuria and bleeding gums were significantly correlated with moderate thrombocytopenia (42.9%, p=0.018; 38.1%, p=0.036, respectively). Bleeding status showed no significant trend across platelet count categories (p=0.198). Conclusions: Thrombocytopenia severity is significantly associated with specific bleeding manifestations in dengue patients, highlighting the need for vigilant platelet monitoring to mitigate complications.